Administration of human resources and the quality of services of the Municipality of Amarilis - Abal-Benancio, Flor F. (2019)
In the present research work, the general objective was to determine the relationship between the Human Resources Administration and the Quality of service to propose a plan with the purpose to improve the quality of services of the Municipality of Amarilis, Period 2015. The investigation was descriptive and correlational, because it measured the degree of relationship between the variables: administration of human resources and quality of service. The sample was 90, administrative workers of the municipality of Amarilis, between the months of October and November in 2015. Related to the instrument of data collection; A questionnaire was applied for each variable. The human resources administration questionnaire was composed of 12 items, with a Likert scale amplitude and quality of service. The validity and reliability of the instrument were determined according to the Cronbach's Alpha coefficient and the results obtained were 0.894, for the questionnaire, therefore, it was reliable and consistent. The results, when applying the Spearman coefficient of relation, show a value of 0.819 which means that there is a high positive correlation, and with respect to the value of "sig." A result of 0.000 was obtained, which is less than 0.05 (level of significance), therefore it is concluded that there is a significant relationship between the Human Resources Administration and the quality of services of the Municipality of Amarilis during the period 2015.